The influence of role overload, role conflict and role ambiguity on occupational stress among nurses in selected Iranian hospitals - Karimi, Roohangiz; Omar, Zoharah; Alipour, Farhad; Karimi, Zinab (Asian Economic and Social Society, 2014)

(untitled)
The aim of this study was to investigate the level of occupational stress and the influence of role overload, role conflict, and role ambiguity on occupational stress among Iranian nurses. This study adopts a quantitative correlational study methodology. The study sample comprised of 135 nurses selected randomly from the emergency and surgery departments at Yasuj hospitals in south west of Iran. The data was collected through self-administrated questionnaire using drop and collect method. The result showed that the level of occupational stress was relatively high. The result also showed that there was a significant, linear and positive relationship between role overload, role conflict, role ambiguity and occupational stress. Finally, multiple regression analysis was used to determine the predictors of occupational stress. About 37% variance in occupational stress was explained by role overload, role conflict, role ambiguity. The result also indicated that role conflict was the strongest predictor to predict occupational stress. The findings of this study provide support to the Job-Demand Control Model and provide practical contribution to alleviate the level of stress among nurses.